2013
DOI: 10.1155/2013/843897
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AngiogenesisIn Vitroby Chebulagic Acid: A COX-LOX Dual Inhibitor

Abstract: Angiogenesis is a crucial step in the growth of cancer and its metastasis. It is regulated by several endogenous factors which may stimulate or inhibit the new blood vessel growth. Besides these endogenous factors, several exogenous factors including some natural compounds are known to modulate angiogenesis. Angiogenesis being a potential target for drugs against a number of pathological conditions, search for compounds from natural sources that can affect angiogenesis is of great interest. The objective of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Docking analysis was validated by in vitro studies, which showed that the activation of Akt by phosphorylation was significantly decreased in cells treated with punicalagin, confirming the involvement of Akt in mediating the anti-angiogenic effect of punicalagin. The anti-angiogenic effect of chebulagic acid has been already reported by our laboratory [15,17]. Chebulagic acid inhibits angiogenesis by downregulating VEGF, VEGFR2, GSK3β, VE-cadherin, and the VE-cadherin-β catenin signaling necessary for the stabilization of endothelial cell-cell adhesion during angiogenesis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Docking analysis was validated by in vitro studies, which showed that the activation of Akt by phosphorylation was significantly decreased in cells treated with punicalagin, confirming the involvement of Akt in mediating the anti-angiogenic effect of punicalagin. The anti-angiogenic effect of chebulagic acid has been already reported by our laboratory [15,17]. Chebulagic acid inhibits angiogenesis by downregulating VEGF, VEGFR2, GSK3β, VE-cadherin, and the VE-cadherin-β catenin signaling necessary for the stabilization of endothelial cell-cell adhesion during angiogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…However, the mechanisms by which THL mediates its anti-tumor actions are still being explored. Earlier in vitro studies using extracts of THL [10], and a study from our laboratory on chebulagic acid (CA), one of the important components of THL, showed an anti-angiogenic effect [15]. CA, a COX/LOX dual inhibitor, is reported to inhibit angiogenesis by modulating the VEGFR2-dependent GSK-3β signaling pathway [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[32], although it has also been isolated from several other plants [33][34][35]. It is reported to exhibit numerous in vitro and/or in vivo bioactivities, including anti-inflammatory [36][37][38], anti-angiogenic [39,40], antitumor [41,42], and glucose uptake regulation properties [43][44][45][46], among others. Chebulagic acid is also reported to exhibit broad-spectrum antiviral activity through interfering with multiple viral targets.…”
Section: Discussionmentioning
confidence: 99%
“…Reduces MDA, an important oxidative stress marker (Seo et al, 2013;Tongtako et al, 2018) Reduction of oxidative stress in AR and may suppress exacerbation of AR-related symptoms Combined with exercise helps increase PNIF, reduce rhinitis symptoms, nasal blood flow, and MDA levels, decreases nasal secretion IL-4, and increase nasal secretion IL-2 levels (Tongtako et al, 2018) Reduce rhinitis symptoms and other nasal symptoms Less decline in pulmonary function when compared to placebo in crossover RCT (Forte et al, 2018) Reduces eosinophil infiltration and increases ratio of IFN-γ/IL-5 cytokines in bronchoalveolar lavage fluid in OVA-challenged mouse model (Chang et al, 2009) Chebulinic acid A strong antioxidant (Lee et al, 2007) Inhibits influenza viral neuraminidase (Li et al, 2020) Reduction of oxidative stress in AR and may suppress exacerbation of AR-related symptoms DNA gyrase inhibitors (Khan et al, 2018) Alleviation of symptoms resulted from viral and bacterial infection in AR patients Chebulagic acid Inhibits enterovirus 71 replication, inhibits influenza viral neuraminidase (Yang et al, 2013) Alleviation of symptoms resulted from viral infection in AR patients Reduces onset and progression of collagen-induced arthritis in mice (reduces serum levels of total and anti-collagen IgG, IL-10, and IL-6 but increases TGF-β) (Lee et al, 2005) Reduction of inflammatory signaling in the airway Inhibits the LPS-induced expression of TNF-α and IL-1β in endothelial cells (Liu et al, 2015) Inhibits COX-2 and 5-LOX enzymes (Reddy et al, 2009;Athira et al, 2013)…”
Section: Gallic Acidmentioning
confidence: 99%